Quantum chemical approaches for controlling and evaluating intramolecular magnetic interactions in organic diradicals. Issue 8 (13th December 2015) - Cho, Daeheum; Ko, Kyoung Chul; Lee, Jin Yong
Abstract : In this review, rational design strategies for pure organic high‐spin molecules with strong intramolecular magnetic interactions are presented, mostly focusing on the design of ferromagnetically coupled organic diradicals. After brief introduction of the calculation procedure for intramolecular magnetic coupling constant J using density functional theory (DFT), classification and standardization of magnetic character of well‐known stable radicals and coupler units are discussed. Following the development of general strategy for the design of organic high‐spin diradical by means of the classification and standardization scheme, applicability of the strategy for making pendent‐type organic polyradical using zigzag graphene nanoribbons backbone is demonstrated. In a computational point of view, a scaling procedure and an optimization of Hartree–Fock exact exchange ratio of a hybrid DFT functional for better prediction of the J of diradicals are discussed. © 2015 Wiley Periodicals, Inc. Abstract : Rational design strategies for organic high‐spin materials are presented by quantum chemical calculations: classification and standardization of radical and coupler units according to the spin alternation rule leads to a general design strategy for ferromagnetic diradicals. Application of the strategy for the design of ferromagnetic polyradicals terminated with organic radicals is discussed. A scaling procedure and modification of hybrid functional for better prediction of the strength of intramolecular magnetic interaction is also discussed.